Prototype Sistem Keamanan Brankas Menggunakan Teknologi RFID Berbasis Arduino Uno - Moh Muthohir; Sendi Prayogi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
In general, the current safes lack a security system and are impractical in accessing them. Looking at the current conditions, most of them still use number combination security, such as the safe security system at Sandimedia, seeing the current situation, the owner of Sandimedia can open the safe, while employees often told to take the files that are in the safe and are often wrong in determining the combination of safe numbers. For the author, this method is less effective for emergency matters. The importance of making a safe opening system using RFID which aims to facilitate user access rights that do not need to rely on number combinations.This data collection method is carried out through several methods aimed at producing certain products and testing the effectiveness of these products. This method is applied to the research procedure into 5 stages (1) literature study, (2) problem analysis, (3) design and realization, (4) testing and measurement (5) discussion methodThe results of the implementation of a security system in safes using a microcontroller-based RFID, the authors can conclude that after system design and testing, it can be seen that RFID technology can be applied to safes as a security system and the use of Radio Frequency Identification (RFID) as a safe safe system runs in accordance with designs and programs that have been made